Modulating the Global Response Regulator, LuxO of V. cholerae Quorum Sensing System Using a Pyrazine Dicarboxylic Acid Derivative (PDCApy): An Antivirulence Approach - Hema, M.; Vasudevan, Sahana; Balamurugan, P.; Adline Princy, S. (Frontiers in Cellular and Infection Microbiology, 2017)
Vibrio cholerae is a Gram-negative pathogen which causes acute diarrhoeal disease, cholera by the expression of virulence genes through quorum sensing (QS) mechanism. The QS circuit of V. cholerae is controlled by the global quorum regulator, LuxO, which at low cell density (LCD) state produces major virulence factors such as, toxin co-regulated pilus (TCP) and cholera toxin (CT) to mediate infection. On the contrary, at the high cell density (HCD) state the virulent genes are downregulated and the vibrios are detached from the host intestinal epithelial cells, promoted by HapA protease. Hence, targeting the global regulator LuxO would be a promising approach to modulate the QS to curtail V. cholerae pathogenesis. In our earlier studies, LuxO targeted ligand, 2,3 pyrazine dicarboxylic acid (PDCA) and its derivatives having desired pharmacophore properties were chemically synthesized and were shown to have biofilm inhibition as well as synergistic activity with the conventionally used antibiotics. In the present study, the QS modulatory effect of the PDCA derivative with pyrrolidine moiety designated as PDCApy against the V. cholerae virulence gene expression was analyzed at various growth phases. The data significantly showed a several fold reduction in the expression of the genes, tcp and ct whereas the expression of hapR was upregulated at the LCD state. In addition, PDCApy reduced the adhesion and invasion of the vibrios onto the INT407 intestinal cell lines. Collectively, our data suggest that PDCApy could be a potential QS modulator (QSM) for the antivirulence therapeutic approach.